SUB PIXEL IMAGE PROCESSING FOR DISTANCE MEASUREMENT ON THE BASE OF DIGITAL CAMERA - V. L. Kozlov; A. S. Vasilchuk (Приборы и методы измерений)
The technique of sub pixel processing of the digital photographic images for precision distances and sizes measurements based on stereogram processing is offered. Experimental results of measuring equipment are presented.